Ritual Ecology and Sirigu Mural Paintings: Interrogating the Intersection of Art and Culture (Journal of Advanced Research in Social Sciences, 2023)
This theoretical research study utilizes qualitative case study research methods to explore the intersection of art and culture in the context of Sirigu mural paintings, a unique art form found in the Upper East region of Ghana. Drawing on the concept of ritual ecology, the study investigates the cultural significance of these paintings and their role in local ritual practices. Through in-depth interviews with artists, community members, and cultural experts, as well as participant observation and visual analysis, the study examines the ways in which Sirigu mural paintings embody and reflect local cultural traditions. The study also analyzes the artistic techniques and materials used in creating the paintings, highlighting the importance of artistic skill and innovation in the production of cultural artifacts. Drawing on theories of cultural identity and cultural transmission, the study examines the ways in which Sirigu mural paintings are passed down through generations and how they contribute to the maintenance and preservation of local cultural practices. Again, the study explores the challenges and opportunities for sustaining cultural heritage in the face of globalization and modernization. The findings of this study contribute to a deeper understanding of the complex relationship between art and culture, and the ways in which cultural practices and traditions are embodied and expressed through artistic forms. Lastly, the study provides insights into the role of artistic innovation and intergenerational transmission in preserving cultural heritage, and the challenges and opportunities for sustaining cultural traditions in a rapidly changing world.